TTZ-SOUTH seismic experiment - T. Янік; В. Старостенко; П. Александровський; Т. Єгорова; В. Чуба; П. Срьода; Г. Муровська; Х. Заяць; К. Коломієць; Д. Лисинчук; Д. Вуйцик; Д. Мечі; et al. (Геофизический журнал, 2021)
The wide-angle reflection and refraction (WARR) TTZ-South transect carried out in 2018 crosses the SW region of Ukraine and the SE region of Poland. The TTZ-South profile targeted the structure of the Earth’s crust and upper mantle of the Trans-European Suture Zone, as well as the southwestern segment of the East European Craton (slope of the Ukrainian Shield). The ~550 km long profile (~230 km in Poland and ~320 km in western Ukraine) is an extension of previously realized projects in Poland, TTZ (1993) and CEL03 (2000). The deep seismic sounding study along the TTZ-South profile using TEXAN and DATA-CUBE seismic stations (320 units) made it possible to obtain high-quality seismic records from eleven shot points (six in Ukraine and five in Poland). This paper presents a smooth P wave velocity model based on first-arrival travel-time inversion using the FAST (First Arrival Seismic Tomography) code. The obtained image represents a preliminary velocity model which, according to the P wave velocities, consists of a sedimentary layer and the crystalline crust that could comprise upper, middle and lower crustal layers. The Moho interface, approximated by the 7.5 km/s isoline, is located at 45—47 km depth in the central part of the profile, shallowing to 40 and 37 km depth in the northern (Radom-Łysogуry Unit, Poland) and southern (Volyno-Podolian Monocline, Ukraine) segments of the profile, respectively. A peculiar feature of the velocity cross-section is a number of high-velocity bodies distinguished in the depth range of 10—35 km. Such high-velocity bodies were detected previously in the crust of the Radom-Łysogуry Unit. These bodies, inferred at depths of 10—35 km, could be allochthonous fragments of what was originally a single mafic body or separate mafic bodies intruded into the crust during the break-up of Rodinia in the Neoproterozoic, which was accompanied by considerable rifting. The manifestations of such magmatism are known in the NE part of the Volyno-Podolian Monocline, where the Vendian trap formation occurs at the surface.